Strategi Pengembangan Usaha Buah Strawberry Beku di Bali Food Industry - ida ayu made dwi susanti; Putu Fajar Kartika Lestari; Ulrikus Rivaldus Nenggo (Universitas Batangahari Jambi, 2023)
Strawberry is one of the potential subtropical fruit commodities to be developed. This study aims to identify internal and external factors in developing a frozen strawberry business in the Bali Food Industry and to analyze the strategy for developing a frozen strawberry business in the Bali Food Industry. Data analysis techniques used IFAS, EFAS, I_E Matrix and SWOT Matrix (Strength, Weakness, Opportunity) and Threats). The results of the study show that the internal factors that influence the Frozen Strawberry Development Strategy in the Bali Food Industry consist of strengths and weaknesses. The strength factor has the same value, namely 0.48 (strong), while the weakness factor is the long delivery process and the unfavorable weather factor is still lacking with each value of 0.12 (weak). External factors consist of opportunities and threats. The opportunity factor has the same value in each statement, namely 0.64 (strong) while the threat factor, namely competing companies, increased production costs and increased consumer bargaining position, is still lacking with each value of 0.16 (weak). The strategy for developing frozen strawberries in the Bali Food Industry consists of maintaining quality according to PSAT standards to meet consumer demand, increasing stock of raw materials to increase production capacity, optimizing production to be able to compete with competing companies, optimizing production to be able to compete with competing companies and increasing capital to increase production capacity.